Tweaking the Structure to Radically Change the Function: The Evolution of Transthyretin from 5-Hydroxyisourate Hydrolase to Triiodothyronine Distributor to Thyroxine Distributor - Richardson, Samantha J. (Frontiers in Endocrinology, 2015)
Often, we elucidate evolutionary processes backwards, starting with eutherian mammals and gradually climbing down the evolutionary tree to those species who have survived since long before mammals evolved. This is also true for elucidating the evolution of specific proteins, in this case the protein currently known as “transthyretin”. Transthyretin (TTR) was first described in eutherian mammals and was known as a thyroxine (T4) binding protein. However, mammals are the exception amongst vertebrates in respect to the function of TTR, as in teleost fish, amphibians, reptiles and birds TTR preferentially binds triiodothyronine (T3), which is the active form of thyroid hormone. The TTR gene possibly arose as a duplication of the TLP (TTR-Like Protein) gene, around the stage of the agnathans. Some vertebrate species have both the TTR and TLP genes, whilst others have “lost” the TLP gene. TLP genes have been found in all kingdoms. The TLPs analysed to date do not bind thyroid hormones or their analogues, but are enzymes involved in uric acid metabolism, specifically, they are 5-hydroxyisourate hydrolases. A Salmonella TLP knock-out strain demonstrated that TLP was essential for the bacteria’s survival in the high uric acid environment of the chicken alimentary tract. Many other TLPs are yet to be characterised for their function although several have been confirmed as 5-hydroxyisourate hydrolases. This review describes the evolution of TLP/TTR and how subtle changes in gene structure or amino acid substitution can drastically change the function of this protein, without altering its overall 3D conformation.